Fate and dynamics of metal precipitates arising from acid drainage discharges to a river system. (December 2018) - Mosley, Luke M.; Biswas, Tapas K.; Dang, Tan; Palmer, David; Cummings, Courtney; Daly, Rob; Simpson, Stuart; Kirby, Jason
Abstract: Neutralisation of acid drainage creates metal-rich precipitates that may impact receiving water bodies. This study assessed the fate of over seven years of acid drainage discharges on the sediments of the lower River Murray (Australia), including the potential for periodic water anoxia to enhance risk via reductive dissolution of amorphous (Fe, Mn and co-precipitated and bound metal) oxide phases. With the exception of one site with restricted water exchange, elevated reducible/reactive metal(oid) (Fe, Ni, As, Co, Zn) concentrations were only observed in the localised wetland-riparian area within approximately 100 m of the discharges. Only a minor exceedance of national sediment quality guideline values occurred for Ni. In the main river channel, elevated reactive metal (Fe, Mn, Ni, Zn) concentrations were also only observed less than approximately 100 m from the drainage discharge point. This appears due to (a) rapid neutralisation of pH leading to metal precipitation and deposition in the localised discharge area, and/or (b) dilution of any metal precipitates entering the main channel with natural river sediments, and/or (c) flushing of precipitates downstream during higher flow conditions. The influence of deoxygenation on metal release was profound with large increases in the concentration of dissolved Fe, Mn, Zn, Ni, and As in the overlying water during laboratory experimental simulations. However, given in situ sediment metal contamination is very localised, it appears on a river reach scale that the acid drainage precipitates will not significantly contribute, over and above, the background release of these metals during these conditions. Graphical abstract: Highlights: Neutralisation of acid drainage produces metal-rich oxide precipitates. The fate of these in a river system under oxic and anoxic conditions was assessed. Contamination was observed in a localised area near the drainage discharge. Ratios of reactive to total recoverable metal were elevated in this zone. Deoxygenation of overlying surface water enhanced metal release.